2020
DOI: 10.3389/fpubh.2020.00006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Health Promotion Interventions on Early Childhood Caries Prevention in Children Aged 2–5 Years Receiving Dental Treatment Under General Anesthesia

Abstract: Aim: This study was conducted to evaluate the impact of health promotion interventions on early childhood caries prevention in 2-5 year-olds receiving dental treatment under general anesthesia.Materials and Methods: Thirty-seven mother-child couples presenting to the clinic of the Dental School of Tehran University of Medical Sciences for treatment under general anesthesia were randomly divided to two groups: 19 couples in the pamphlet and fluoride varnish four times a year, and 18 couples in the pamphlet plus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 22 publications
3
10
0
4
Order By: Relevance
“…Promotion of health is a necessary action that should be carried out at all ages, as it may trigger benefits both in terms of disease risk reduction and prevention, regardless of the phase of life [1,2]. Such benefits become even more evident if health is fostered from youth [3].…”
Section: Introductionmentioning
confidence: 99%
“…Promotion of health is a necessary action that should be carried out at all ages, as it may trigger benefits both in terms of disease risk reduction and prevention, regardless of the phase of life [1,2]. Such benefits become even more evident if health is fostered from youth [3].…”
Section: Introductionmentioning
confidence: 99%
“…The rates of failure of restorations following general anesthesia, however, seem to suggest that there is a risk of failure even after pulpectomies were performed [ 8 , 12 , 15 ]. Studies from across the globe have shown that while general anesthesia improves the oral health-related quality of life of children, the most significant predictor of success is the implementation of good postoperative oral hygiene and parental oral health promotion [ 8 , 22 – 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bukan hanya di Indonesia laporan terbaru mengenai kesehatan mulut di Iran menunjukan prevalensi tinggi karies pada anak-anak prasekolah lebih dari 87% anak usia 5-6 tahun dengan dmft rata-rata 5,16 dan komponen terdiri lebih dari 70% dari total mean. Razeghi, (2020). Dilihat dari angka ini membuktikan bahwa masih rendahnya kesadaran masyarakat mengenai kesehatan gigi dan mulutnya.…”
Section: Tinjauan Pustakaunclassified
“…Karies gigi pada anak prasekolah menimbulkan resiko yang jelas terhadap kesehatan umum sebagai penyakit umum pada anak-anak, selain itu penyakit ini dikaitkan dengan dampak fungsional, estetika dan psikologiis yang nyata pada kualitas hidup anak keluarga dan membebani biaya yang tinggi. Razeghi (2020). Chomaria (2015) mengungkapkan "Lubang gigi disebut juga karies gigi disebabkan karena infeksi bakteri.…”
Section: Tinjauan Pustakaunclassified